Alternative spatial hierarchies: a cross-border spouse's positioning strategies in the face of Germany's 'pre-integration' language test. Issue 2 (25th January 2021) - Jashari, Shpresa; Dahinden, Janine; Moret, Joëlle
ABSTRACT: This paper examines how spouses waiting in Turkey to be reunited with their partner in Europe experience border regimes and deal with the transnationalised discourses on 'marriage migrants' they encounter. It is based on the analysis of a single narrative interview, that of a woman taking German classes at Goethe Institute in Istanbul in order to pass the required language test. Like other respondents, she is confronted with negative gendered preconceptions regarding 'Turkish import brides'. Her boundary work involves mobilising alternative hierarchies in an attempt to discursively construct a different Turkey than the one generally represented: she draws on social class (positioning herself as a member of the highly educated, mobile and economically better off), socio-spatial units (focusing on her urbanity) and gender (experiencing 'modern' and equal gender relationships). The paper emphasises the importance of the socio-spatial context, here the classroom, where boundary-making takes place. It also provides insights into the effects of global spatial hierarchies on migrants and their alternative narratives, a dimension that can only be understood through a decentred analysis. The article contributes to studies on cross-border marriages by analysing the 'outgoing' side, a perspective still rarely addressed in the literature.